Effectiveness of Teacher Professionalism in The Science Process Skills of Students - Qodriyani, Hidayah Ina; Aloysius, Suyitno; Suyanto, Slamet (JPI (Jurnal Pendidikan Indonesia), 2020)
The scientific ability of students who are under international average standards compels them to continuously improve education quality in Indonesia. The inequality understanding of scientific process skills in districts like in Sragen is worth the attention. Teachers as the education core should be able to professionally develop the scientific process skills of participants. The research aims to determine the professional influence of teachers on the skills, including knowing the profile of the skills, mastery of the skills’ aspects. This research is a quantitative descriptive survey. The study was conducted on 198 students and biology teachers. Collecting student data with tests and teachers with questionnaires and interviews. Results show the skills in Sragen categorized as medium to average 19.22 of 32, the highest mastery of the skills’ aspects are communicating and predicting, the lowest is identifying variables, collecting and processing data, there is a professional influence of teachers on the skills.